Palladium-catalyzed [4 + 4] cycloadditions for highly diastereo- and enantioselective synthesis of functionalized benzo[b]oxocines. Issue 13 (19th May 2022) - Wang, Xunhua; Yang, Jianfeng; Lv, Ruifeng; Song, Pengfei; Ye, Denghui; Liu, Jitian; Li, Xiaoxun
Abstract : An efficient palladium-catalyzed asymmetric [4 + 4] cycloaddition of highly reactive ortho -quinone methides with γ-methylidene-δ-valerolactones for the construction of functionalized eight-membered benzo[ b ]oxocine derivatives has been developed. Abstract : Asymmetric cycloaddition reactions represent a powerful strategy for building up complex molecular architectures, especially those with medium-sized rings. Herein, we disclose a highly diastereo- and enantioselective cycloaddition strategy that involves the palladium-catalyzed [4 + 4] cycloaddition between ortho -quinone methides and γ-methylene-δ-valerolactones. This method provided a straightforward and applicable approach to access various functionalized benzo[ b ]oxocines bearing adjacent all-carbon quaternary and tertiary stereocenters (38 examples, up to 95% yield, 20 : 1 dr, 98% ee). The process was efficient and scalable, and the products could be further transformed to various chiral eight-membered molecules. In addition, DFT calculations were performed to shed light on the mechanism of good stereoselectivities.